Dried Leaves Powder of Adiantum capillus-veneris as an Efficient Biosorbent for Hazardous Crystal Violet Dye from Water Resources - Salma Gul; Shehla Gul; Hajera Gul; Fatima Khitab; Rozina Khattak; Muhammad Sufaid Khan; Rizwan Ullah; Rooh Ullah; Zahida Wasil; Andrey E. Krauklis; Ivar Zekker (Separations, 2023)
The dyeing industry uses many chemicals and dyes. After the dying process is completed, they release a significant amount of dyes in wastewater. The dyes’ color emissions are extremely poisonous and dangerous for aquatic and terrestrial life. Due to the toxic nature of dyes, the current study was carried out to evaluate whether it would be effective to employ an adsorption procedure with leaves from the Adiantum capillus-veneris plant as an adsorbent to remove commonly used textile dyes from an aqueous dye solution and wastewater. The effect of pH, concentration, time and the adsorbent dose on the adsorption process was studied in order to determine the maximum adsorption under ideal conditions. The selected pH was 3; the optimum concentration was 30 ppm with a contact time of 90 min and the optimized adsorbent dose was 60 mg. The absorbent under study showed excellent results when compared with commercial adsorbents i.e., animal charcoal and silica gel. The leaves of the Adiantum capillus-veneris plant revealed a maximum removal of 90.36 percent crystal violet dye (adsorption capacity (Qe) 9.05 mg/g) without any treatment to activate or alter the surface chemistry of the biosorbent. Its effectiveness was also tested with water gathered from several sources, including canal water, tap water, distilled water, and saline water, to determine whether it was practical. In both the canal and the tap water, the adsorbent displayed good removal efficiency. From the results of the current study, it can be inferred that the leaves of the Adiantum capillus-veneris plant are a reasonably priced biosorbent that can be used to remove toxic dyes from wastewater to protect water bodies from toxic pollution and can be used to treat industrial wastewater directly.